Icts teaching resources for the development of autonomous learning of english language in the students of tercer año de bachillerato, at unidad educativa a distancia de Chimborazo extensión Chunchi - Capsol, Chimborazo province, during the school year 2014 -2015 - Calle Luna, Lourdes (2016)
Chimborazo extensión Chunchi – Capsol, Chimborazo province during the school year 2014 -2015.” This research has been designed under the rules established by the Facultad de Ciencias de La Educación, Humanas y Tecnologías which follows the same scheme granted by the research team of the faculty.